Mutant p53 in Cancer Progression and Targeted Therapies - Zhu, Gaoyang; Pan, Chaoyun; Bei, Jin-Xin; Li, Bo; Liang, Chen; Xu, Yang; Fu, Xuemei (Frontiers in Oncology, 2020)
TP53 is the most frequently mutated gene in human cancers with a mutational frequency over 50% of all human cancers. Most of these p53 gene mutations are missense mutations, leading to the expression of the p53 mutant proteins. Mutant p53 proteins not only lose wild-type p53-dependent tumor suppressive functions, but also frequently acquire oncogenic gain of functions (GOF) that promote tumorigenesis. Intensive investigation of the oncogenic gain of functions of p53 mutants will accelerate the development of targeted therapies for human cancers harboring mutant p53. In this review, we summarize the recent advances in our understanding of the oncogenic functions of mutant p53 and the potential therapies targeting mutant p53 in human cancers.